Neural ECM molecules in axonal and synaptic homeostatic plasticity - Frischknecht, Renato; Chang, Kae-Jiun; Rasband, Matthew N.; Seidenbecher, Constanze I. (Progress in Brain Research, 2014)
Neural circuits can express different forms of plasticity. So far, Hebbian synaptic plasticity was considered the most important plastic phenomenon, but over the last decade, homeostatic mechanisms gained more interest because they can explain how a neuronal network maintains stable baseline function despite multiple plastic challenges, like developmental plasticity, learning, or lesion. Such destabilizing influences can be counterbalanced by the mechanisms of homeostatic plasticity, which restore the stability of neuronal circuits. Synaptic scaling is a mechanism in which neurons can detect changes in their own firing rates through a set of molecular sensors that then regulate receptor trafficking to scale the accumulation of glutamate receptors at synaptic sites. Additional homeostatic mechanisms allow local changes in synaptic activation to generate local synaptic adaptations and network-wide changes in activity, which lead to adjustments in the balance between excitation and inhibition. The molecular pathways underlying these forms of homeostatic plasticity are currently under intense investigation, and it becomes clear that the extracellular matrix (ECM) of the brain, which surrounds individual neurons and integrates them into the tissue, is an important element in these processes. As a highly dynamic structure, which can be remodeled and degraded in an activity-dependent manner and in concerted action of neurons and glial cells, it can on one hand promote structural and functional plasticity and on the other hand stabilize neural microcircuits. This chapter highlights the composition of brain ECM with particular emphasis on perisynaptic and axonal matrix formations and its involvement in plastic and adaptive processes of the central nervous system.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Agrin; Axon initial segment; Brevican; Dystroglycan; Lecticans; Narp; Nodes of Ranvier; Perineuronal net; Synaptic scaling